Evaluating the Iberian Exception’s impact on electricity markets - Izac, Nicolas; Sadílek, Tomáš; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The thesis explores the Iberian Exception (IE), a temporary mechanism implemented in Spain and Portugal between June 2022 and December 2023 to mitigate the effects of soaring natural gas prices on electricity markets. Triggered by the 2021–2022 energy crisis and the EU’s dependency on Russian gas, the IE sought to reduce the influence of gas prices on electricity costs by compensating certain fossil-fuel-based power plants in exchange for limiting their market bids. Spain’s limited interconnection with the rest of Europe and its heavy reliance on the spot electricity market made it particularly vulnerable to energy price shocks. The European Commission recognized this structural fragility and allowed Spain and Portugal to adopt exceptional measures. While Spanish authorities highlighted the IE’s positive effects, some studies questioned its real benefits, particularly regarding its long-term efficiency and consumer savings. This thesis aims to clarify these divergent evaluations through an analysis of methodologies and assumptions used in existing studies. It addresses the following research question: “Has the Iberian Exception (IE) been properly assessed, taking into account the gas decoupling, the price elasticity of demand among small consumers, and the spillover effects on French spot market prices?” By examining market coupling mechanisms and elasticity effects, the study seeks to determine whether the IE truly achieved its intended goals and to what extent it can inform future European electricity market reforms.
Vedoucí práce: Tomáš Sadílek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses